2023
DOI: 10.1021/acscentsci.2c01513
|View full text |Cite
|
Sign up to set email alerts
|

Computational Protein Design for COVID-19 Research and Emerging Therapeutics

Abstract: As the world struggles with the ongoing COVID-19 pandemic, unprecedented obstacles have continuously been traversed as new SARS-CoV-2 variants continually emerge. Infectious disease outbreaks are unavoidable, but the knowledge gained from the successes and failures will help create a robust health management system to deal with such pandemics. Previously, scientists required years to develop diagnostics, therapeutics, or vaccines; however, we have seen that, with the rapid deployment of high-throughput technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…The insights obtained from this study are invaluable in understanding the distinct structural, dynamic, and binding attributes of BA.1, BA.4/5, and BF.7 variants. Moreover, these findings have implications for comprehending the molecular mechanisms of other SARS-CoV-2 variants/subvariants and can contribute to the development of targeted therapeutics …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The insights obtained from this study are invaluable in understanding the distinct structural, dynamic, and binding attributes of BA.1, BA.4/5, and BF.7 variants. Moreover, these findings have implications for comprehending the molecular mechanisms of other SARS-CoV-2 variants/subvariants and can contribute to the development of targeted therapeutics …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these findings have implications for comprehending the molecular mechanisms of other SARS-CoV-2 variants/subvariants and can contribute to the development of targeted therapeutics. 39 …”
Section: Discussionmentioning
confidence: 99%
“…In our recent studies, we harnessed the power of high-throughput protein design methodologies to pinpoint critical residues and mutations within intracellular proteins including main protease (M pro ), RdRp, and spike protein receptor binding domain (RBD) of SARS-CoV-2, which could make the virus more tolerant and adaptable to antiviral drugs such as remdesivir, molnupiravir, favipiravir, nirmatrelvir and bebtelovimab. 21–26 While conducting this research, we found that mutational and residue-specific changes can induce relative stabilities and adaptability of the RdRp, for instance, the nsp7 by forming symmetrical dimers. 20 This realization prompted us to perform an extensive protein design and ML-based endeavour, which was further complemented by a comprehensive multi-parametric analysis.…”
Section: Introductionmentioning
confidence: 93%
“…Alterations to the spike protein's binding affinity and specificity for ACE2 can have an impact on the pathogenicity and transmission of viruses [84]. For instance, the RBD of the spike protein has several changes in the B.1.1.7 variation, including N501Y, which has been demonstrated to increase the binding affinity for ACE2 and improve viral infectivity [85]. Similar to the B.1.351 variant, the B.1.351 variant features many mutations in the RBD, including E484K, which decreases the binding affinity for some monoclonal antibodies and might have an impact on how well the host immune system neutralizes the virus [19,86].…”
Section: Changes In Spike Protein Receptor Binding Affinity and Speci...mentioning
confidence: 99%